ESOPHAGEAL STRICTURES FOLLOWING ESOPHAGEAL ATRESIA REPAIR IN CHILDREN IN SULAIMANI CITY; FREQUENCY AND RESPONSE TO ENDOSCOPIC BALLOON DILATATION - Hasan, Adnan Mohammed; Marif, Mahdi Aziz Hama; Sediq, Rozhan Nabaz M. (Journal of Sulaimani Medical College, 2020)
Background Anastomotic stricture is the main complication after surgical repair of esophageal atresia and balloon dilatations remain the treatment of choice for symptomatic esophageal strictures. Objectives The aim of this study was to evaluate the frequency of anastomotic stricture and the efficacy and complications of esophageal balloon dilatations for symptomatic anastomotic stricture in children with esophageal atresia treated in our center. Patients and Methods The medical records of 28 children operated on for esophageal atresia type C (Gross) over a 6-year period were retrospectively reviewed. Results Anastomotic stricture developed in 6 (21.4%) of the patients. They were submitted to 17 dilatation sessions. Stricture resolution occurred after a mean dilatation of 2.83 per patient (range, 1-7). Dilation was successful in 100% of patients. No complications were happened during or after the dilatation sessions. Conclusions Anastomotic stricture, secondary to the surgical treatment of esophageal atresia, is a common complication in patients with esophageal atresia. Esophageal dilation with balloon dilators is an effective and very safe procedure in the management of strictures.
Keywords: Esophageal atresia; Esophageal dilatation; Anastomotic Stricture